Competency-based time-variable training internationally: Ensuring practical next steps in the wake of the COVID-19 pandemic. (3rd July 2021) - Schumacher, Daniel J.; Caretta-Weyer, Holly; Busari, Jamiu; Carraccio, Carol; Damodaran, Arvin; Gruppen, Larry D.; Hall, Andrew K.; Kinnear, Benjamin; Warm, Eric; Ten Cate, Olle; ,
Abstract: Competency-based medical education has been advocated as the future of medical education for nearly a half-century. Inherent to this is the promise that advancement and transitions in training would be defined by readiness to practice rather than by time. Of the logistical problems facing competency-based, time-variable (CBTV) training, enacting time variability may be the largest hurdle to clear. Although it is true that an 'all or nothing' approach to CBTV training would require massive overhauls of both medical education and health care systems, the authors propose that training institutions should gradually evolve within their current environments to incrementally move toward the best version of CBTV training for learners, supervisors, and patients. In support of this evolution, the authors seek to demonstrate the feasibility of advancing toward the goal of realistic CBTV training by detailing examples of successful CBTV training and describing key features of initial steps toward CBTV training implementation.